Metabolic Syndrome: Its Association with Acute ST-Elevation Myocardial Infarction and Its Clinical Outcome – A Study Done in the Tertiary Level Hospital in Bangladesh - Huda, Reaz Mahmud; Mozaffor, Miliva; Alam, Mohammad Ashraful; Hossain, Md Delwar (International Journal of Human and Health Sciences (IJHHS), 2020)
Background:Metabolic syndrome is a matter of immense public health concern. Based on ethnicity, its associationand impact on ischemic heart diseases like myocardial infarction (MI) is a current topic of research. Objective: To evaluate the clinical impact of metabolic syndrome on patients with acute ST-elevation myocardial infarction (acute STEMI) in a Bangladeshi population. Methods: This prospective observational study was done in the Department of Cardiology of the National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, from July to December of 2013.A total 233 patient were selected for data collection; 109 were in group I (acute STEMI patients with metabolic syndrome), while 124 werein group II (acute STEMI patients without metabolic syndrome). Initial evaluation of the patients done by history and clinical examination was recorded in the preformed data collection sheet.Baseline investigations like ECG, CK(MB), lipid profile, fasting blood sugar, serum creatinine andechocardiography were done. Coronary angiogram (CAG) was done in the Cardiac Cath-Lab facility of the same hospital.The patients’ outcomes were observed until they were discharged from the hospital. Results: Heart failure was significantly more in patients of group I than group II (46.79% vs. 20.97%; p<0.001). Among the patients who underwent coronary angiogram (CAG), the mean Friesinger score was 9.7±2.5 in group I and 7.1±3.3 in group II, which was statistically significant (p<0.05), and indicated more chances of severe coronary artery disease in group I patients. However, mortality rate was not statistically significant in between group I and group II (16.51% vs 12.09%; p=0.415). Both in heart failure and coronary artery disease, among all the components of metabolic syndrome, hyperglycemia had the strongest association followed by low HDL and high triglyceride (TG). However, raised BP had much less significant association with development of heart failure or coronary artery disease. Conclusion:Our data suggest that the acute ST-elevation myocardial infarction patients with metabolic syndrome have poor disease prognosis and in-hospital outcome than those without metabolic syndrome.However, the use of a simple risk score based on those biomarkers may identify a high-risk group to initiate preventive measures for cardiovascular health of the country’s population. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 215-221